Zdravstvo v Sloveniji = Shëndeti në Slloveni = Здравоохранение в Словении Informacije za nove prebivalce = Mjet informativ për banorët e rinj = Информационный инструмент для новых жителей - Marin, Nina (ZRC SAZU, Založba ZRC, 2018)
This multilingual booklet presents a section of a comprehensive information platform on living and working in eight countries of the Danube region called DANUBE COMPASS. It provides an overview of basic information for easier orientation within the Slovenian healthcare system. Zdravje v Sloveniji is intended for users that are not familiar with the Slovenian healthcare system and are facing language barriers as well as for healthcare professionals who want to improve access to information and services for non-Slovenian speakers.